STRATEGI PENYELESAIAN KONFLIK MASYARAKAT KAWASAN TAMBANG BATUBARA DI SEUNAGAN NAGAN RAYA - Muffaruddin; Salim, Agus; Tjoetra, Afrizal (FISIP Universitas Malikussaleh, 2025)
Land conflict in the coal mining area of PT. Bara Energi Lestari in Gampong Alue Buloh, Seunagan District, Nagan Raya Regency, shows the complexity that involves various interests of the community and companies. This research aims to identify effective conflict resolution strategies through a qualitative approach with case studies. Data was obtained from literature studies and in-depth interviews with citizens, company representatives, and government officials. Ralf Dahrendorf's conflict theory is used to analyze the dynamics of power relations between the actors involved. The results of the study show that conflicts are resolved through mediation facilitated by the police, involving the community and the company. An agreement was reached on the priority of recruiting workers from local residents and transparency in the use of corporate social responsibility (CSR) funds. This strategy emphasizes the importance of active community participation, information disclosure, and long-term commitment from all parties. A dialogical and collaborative approach has been shown to be more effective in reducing tensions, building trust, and creating sustainable solutions. These findings recommend the need to strengthen local mediation mechanisms in resolving agrarian conflicts in industrial areas, especially those related to mining.